Workshop Teknik Penulisan Karya Ilmiah Bagi Guru di SMA Negeri 1 Lubuk Dalam - Kurniawan, Edi; Trisna, Meyci; Hartati, Nina; Sumarna, Herlin; Okviyanto, Toni; Ramadhoni, Tri Satya (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Scientific work is a form of scientific publication used by teachers to support the Sustainable Professional Program (PKB) that has been launched by the government to actualize the work of teachers as professional staff. Many teachers do not understand how to make a good and correct scientific work, even though scientific work is a mandatory requirement for teachers for the promotion process. The implementation of community service activities aims to provide workshops on scientific writing techniques for teachers at SMA Negeri 1 Lubuk Dalam. The strategy used is through lecture, tutorial, and discussion methods and observation sheets to see the effectiveness of the methods used. The result of this dedication is that the teacher is able to understand the techniques of writing scientific papers well and correctly so that they are suitable for publication